Ion Acceleration by Ultra-intense Laser Pulse Interacting with Double-layer Near-critical Density Plasma. (March 2016) - Gu, Y. J.; Kong, Q.; Kawata, S.; Izumiyama, T.; Nagashima, T.; Takano, M.; Li, X. F.; Yu, Q.; Barada, D.; Ma, Y. Y.; Wang, P. X.
Abstract: A collimated ion beam is generated through the interaction between ultra-intense laser pulse and a double layer plasma. The maximum energy is above 1GeV and the total charge of high energy protons is about several tens of nC/μm. The double layer plasma is combined with an underdense plasma and a thin overdense one. The wakefield traps and accelerates a bunch of electrons to high energy in the first underdense slab. When the well collimated electron beam accelerated by the wakefield penetrates through the second overdense slab, it enhances target normal sheath acceleration (TNSA) and breakout after-burner (BOA) regimes. The mechanism is simulated and analyzed by 2.5 dimensional Particle-in-cell code. Compared with single target TNSA or BOA, both the acceleration gradient and energy transfer efficiency are higher in the double layer regime.